Comparison of radiation exposure during transradial diagnostic coronary angiography with single‐ or multi‐catheters approach. Issue 2 (10th November 2016) - Plourde, Guillaume; Abdelaal, Eltigani; MacHaalany, Jimmy; Rimac, Goran; Poirier, Yann; Arsenault, Jean; Costerousse, Olivier; Bertrand, Olivier F.
Abstract : Objective: To compare radiation exposure during transradial diagnostic coronary angiography (DCA) using standard single‐ or multi‐catheters with different shapes. Background: Transradial DCA can be performed using single‐ or multi‐catheters to canulate left and right coronary ostia. To date, it remains unknown whether there are differences in radiation exposure between the two strategies. Methods: From November 2012 to June 2014, 3, 410 consecutive patients who underwent transradial DCA were recruited. Groups were based on the initial diagnostic catheter used and were dichotomized between single‐ and multi‐catheters approach. All crossovers were excluded. The multi‐catheters approach (Multi) group consisted of Judkins left and right catheters, whereas the single‐catheter (Single) group included Amplatz, Barbeau, or Multipurpose catheters. Fluoroscopy time (FT) as a surrogate end‐point for total radiation exposure and kerma‐area product (KAP; patient radiation exposure) were collected as radiation exposure parameters. Results: A single‐catheter strategy was used in 439 patients, while 2, 971 patients had a multi‐catheters approach. There was no significant difference in FT between groups (2.86 ± 1.48 min for Multi vs. 2.87 ± 1.72 min for Single, P  = 0.13). The multi‐catheters approach was associated with a significant 15% reduction in KAP (3, 599 ± 2, 214 cGy · cm 2 vs. 3, 073 ± 1, 785 cGy · cm 2, P  < 0.0001) compared to the single‐catheter approach. When pooling all patients, mean FT was 2.86 ± 1.51 min. Mean KAP was 3, 141 ± 1, 854 cGy · cm 2 . Reference levels in our institution in both groups were below international diagnostic reference levels. Overall both FT and KAP decreased by 15% and 19%, respectively, over the 2‐year study period. Conclusions: Compared to a single‐catheter approach, a multi‐catheters approach with standard Judkins catheters for DCA significantly reduced patient radiation exposure. Whether single catheter designed for DCA by radial approach can further reduce radiation exposure compared to Judkins catheters remains to be compared in randomized studies. © 2016 Wiley Periodicals, Inc.